Green and Low-Carbon Development Path of Boiler Equipment in China - Li Jun; Da Yaodong; Liu Xuemin; Yu Jiming; Chang Yongqiang; Hou Nana (中国工程科学, 2022)
As special equipment with high energy consumption, boilers are widely used in electric power, heating, steel, and other industries and in daily life. It is a significant infrastructure for guaranteeing economic development and people’s life. Energy consumption, air pollutants, and carbon emissions of boilers are large. Therefore, green and low-carbon transformation of boiler equipment is crucial for realizing carbon peak and carbon neutrality. In this paper, power station boilers and industrial boilers are discussed separately from the perspective of energy conservation and carbon emission reduction of boiler equipment, the development trend of boiler equipment in China is summarized, and existing problems are analyzed. Based on the characteristics of the power station and industrial boilers, and considering the stages of production, use, and inspection, as well as the factors of fuel supply, operating conditions, and operation level, green and low-carbon development paths of boiler equipment are proposed, including upgrade of power station boilers, low-carbon transformation of industrial boilers, green development of boiler manufacturing, and use and management level improvement. Moreover, corresponding measures are expounded. Finally, countermeasures and suggestions are proposed from three aspects: strengthening scientific and technological innovation, perfecting public service system, and improving laws, regulations, and standards system, so as to provide a reference for promoting the transformation and upgrading of the boiler equipment manufacturing industry and realizing the green and low-carbon development of boiler equipment.